1993
DOI: 10.1111/j.1469-8137.1993.tb03871.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the host on three sub‐Arctic annual facultative root hemiparasites

Abstract: SUM M A H YGrowth, mineral accumulation and above-ground dry-matter partitioning were measured in three sub-Arctic annual facultative root hemiparasites, Rhinanthus minor L., Euphrasia frigida L. and Melanipyrum sylvatictivi L., growing either unattached or attached to a host plant. Attached plants were at least an order of magnitude taller than unattiiched plants, and indi\ iduals produced n total abo\ e-ground biomass up to three orders of magnitude greater than that produced by unattached plants. Attached p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 27 publications
5
46
0
Order By: Relevance
“…This may be related to the fact that there were no consistent eects of the dierent hosts on the nitrogen concentration of the parasite. In contrast, strong stimulation of parasite growth by legumes has been found for a number of hemiparasites and been related to greater availability of nitrogen in leguminous hosts (Govier et al 1967;Seel and Press 1993; but see Marvier 1996). Nitrogen concentration of the parasite was also not signi®cantly increased by high nutrient levels.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This may be related to the fact that there were no consistent eects of the dierent hosts on the nitrogen concentration of the parasite. In contrast, strong stimulation of parasite growth by legumes has been found for a number of hemiparasites and been related to greater availability of nitrogen in leguminous hosts (Govier et al 1967;Seel and Press 1993; but see Marvier 1996). Nitrogen concentration of the parasite was also not signi®cantly increased by high nutrient levels.…”
Section: Discussionmentioning
confidence: 80%
“…Hemiparasites growing with nitrogenrich hosts (e.g. legumes) often have greater concentrations of nitrogen, higher rates of photosynthesis and better growth than those growing with nitrogen-poor hosts (Seel and Press 1993;but see Marvier 1996). The loss of water and solutes to a hemiparasite can strongly reduce the growth of the host plants, especially when nutrients are limiting (Malcolm 1964;Gibson and Watkinson 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Increased nitrogen availability may be responsible for the great increase in seed production. Several other studies have found that hemiparasites are most successful on leguminous hosts compared to nonlegumes or grasses (Gibson and Watkinson 1989, Seel and Press 1993, Matthies 1996, Press and Seel 1996, Marvier 1998a, Adler 2002, suggesting that hemiparasites may be nitrogenlimited. In addition to this direct effect, resources from lupine hosts may be responsible for strong differences in pollinator attraction via increased floral display (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Increased parasite performance on certain host species may be due in part to greater availability of resources from those hosts. For example, legumes differ from nonleguminous hosts in their ability to fix nitrogen (via association with symbionts) and the greater performance of many parasitic plants on leguminous hosts is generally attributed to increased nitrogen availability (Gibson and Watkinson 1989, Seel and Press 1993, Matthies 1996, Press and Seel 1996, Marvier 1998a, Adler 2002. In addition to direct effects, host species may also indirectly affect parasitic plant success by altering interactions between the parasite and its community of mutualists, such as pollinators, and antagonists, such as herbivores.…”
Section: Introductionmentioning
confidence: 99%
“…The hemiparasites show considerable host-dependent variation in their light saturated rates of photosynthesis (Fig. 1 a, b, c, see also Seel et al. 1993).…”
Section: Discussionmentioning
confidence: 97%